Measuring quality of life after intensive care using the Arabic version for Morocco of the EuroQol 5 Dimensions - Khoudri Ibtissam; Belayachi Jihane; Dendane Tarek; Abidi Khalid; Madani Naoufel; Zekraoui Aicha; Zeggwagh Amine Ali; Abouqal Redouane (BMC Research Notes, 2012)
Abstract Background Health-related quality of life (HRQL) is a relevant outcome measures in intensive care unit (ICU). The aim of this study was to evaluate HRQL of ICU patients 3 months after discharge using the Arabic version for Morocco of the EuroQol-5-Dimension (EQ-5D), and to examine the psychometric properties of the questionnaire. Results The Arabic version for Morocco of the EQ-5D was approved by the EuroQol group. A prospective cohort study was conducted after medical ICU discharge. At 3-month follow up, the EQ-5D (self classifier and EQ-VAS) was administered in consultation or by telephone. EQ-VAS varies from 0 (better HRQL) to 100 (worst HRQL). An unweighted scoring for EQ5D-index was calculated. EQ5D-index ranges from -0.59 to 1. Test-retest reliability of the EQ-5D was tested using Kappa coefficient and intraclass correlation coefficient (ICC). Criterion validity was assessed by correlating EQ-VAS and EQ5D-index with the Short Form 36 (SF-36). Construct validity was tested using simple and multiple liner regression to assess factors influencing patients'HRQL. 145 survivors answered the EQ-5D. Median EQ5D-index was 0.52 [0.20-1]. Mean EQ-VAS was 62 ± 20. Test-retest reliability was conducted in 83 patients. ICCs of EQ5D-index and EQ-VAS were 0.95 and 0.92 respectively. For EQ-5D self classifier, agreement by kappa was above 0.40. Significant correlations were noted between EQ5D-index, EQ-VAS and SF-36 (p < 0.001). In multivariate analysis, factors associated with poorer HRQL for EQ5D-index were longer ICU length of stay (β = -0.01; p = 0.017) and higher educational level (β = -0.2; p = 0.001). For EQ-VAS men were associated with better HRQL (β = 6.5; p = 0.048). Conclusions The Arabic version for Morocco of the EQ-5D is reliable and valid. Women, high educational level and longer ICU length of stay were associated with poorer HRQL.